2015
DOI: 10.1186/s12990-015-0043-0
|View full text |Cite
|
Sign up to set email alerts
|

Function and Postnatal Changes of Dural Afferent Fibers Expressing TRPM8 Channels

Abstract: BackgroundGenome-wide association studies have identified TRPM8 (transient receptor potential melastatin 8) as one of the susceptibility genes for common migraine. Here, we investigated the postnatal changes of TRPM8-expressing dural afferent fibers as well as the function of dural TRPM8 channels in mice.ResultsFirst, we quantified the density and the number of axonal branches of TRPM8-expressing fibers in the dura of mice expressing farnesylated enhanced green fluorescent protein (EGFPf) from one TRPM8 allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…This result was confirmed in subsequent studies of large cohorts that also analyzed additional TRPM8 SNPs, finding rs6741751 as the most significant SNP ( P = 9 × 10 −14 ) . The mechanism underlying this association has not been adequately explored, although TRPM8 channels are known to be expressed in trigeminal afferents, and form complexes with 5‐HT 1B receptors with amplified analgesic function . Further, activation of dural TRPM8 has been associated with the development of sumatriptan‐responsive facial allodynia in rats …”
Section: Introductionmentioning
confidence: 78%
“…This result was confirmed in subsequent studies of large cohorts that also analyzed additional TRPM8 SNPs, finding rs6741751 as the most significant SNP ( P = 9 × 10 −14 ) . The mechanism underlying this association has not been adequately explored, although TRPM8 channels are known to be expressed in trigeminal afferents, and form complexes with 5‐HT 1B receptors with amplified analgesic function . Further, activation of dural TRPM8 has been associated with the development of sumatriptan‐responsive facial allodynia in rats …”
Section: Introductionmentioning
confidence: 78%
“…Using FG to label dural afferent neurons in TRPM8 EGFPf/+ mice, we found that only 3%‐4% of dural afferent neurons express TRPM8 channels in adult mice, much lower than the percentage of total TG neurons expressing TRPM8 (10%). This is surprising, given that activation of dural TRPM8 channels significantly modifies headache‐related behaviors in rodent models . It is possible that we may underestimate the abundance of dural afferent neurons expressing TRPM8, as we removed the muscle and periosteal sheath on the skull before tracer application.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we have measured the abundance of dural afferent neurons that express neuropeptide calcitonin gene‐related peptide (CGRP), transient receptor potential (TRP) channel subfamily V member 1 (TRPV1) and subfamily A member 1 (TRPA1), respectively . However, using fluorescent retrograde tracer DiI (1,1′‐dioctadecyl‐3,3,3′,3′‐tetramethylindocarbocyanine perchlorate), we were not able to label the cell body of dural afferent neurons expressing TRP channel melastatin 8 (TRPM8) in mouse trigeminal ganglion (TG), despite the fact that TRPM8‐expressing fibers are known to be present on mouse dura and dural TRPM8 channels have been shown to regulate headache‐related behaviors in rodent models . This presents a technical hurdle for further investigation of the neurochemical and physiological properties of TRPM8‐expressing dural afferent neurons.…”
Section: Background and Objectivementioning
confidence: 96%
See 1 more Smart Citation
“…Sparse innervation of the EGFP‐positive, TRPM8‐expressing fibers are observed in some areas of the dura in adult mice . Interestingly, both the density and the number of axonal branches of dural fibers expressing TRPM8 are decreased substantially from postnatal day 2 (P2) to adulthood . The reduction occurs before the onset of puberty (P25) in both male and female mice, and is independent of the expression and/or the activation of TRPM8 channels per se.…”
Section: The Expression Of Trpm8 Channels and The Projection Of Trpm8mentioning
confidence: 99%